Pre- and Postnatal Predator Cues Shape Offspring Anti-predatory Behavior Similarly in the Bank Vole - Sievert, Thorbjörn; Bouma, Kerstin; Haapakoski, Marko; Matson, Kevin D.; Ylönen, Hannu (Frontiers in Ecology and Evolution, 2021)
Prey animals can assess the risks predators present in different ways. For example, direct cues produced by predators can be used, but also signals produced by prey conspecifics that have engaged in non-lethal predator-prey interactions. These non-lethal interactions can thereby affect the physiology, behavior, and survival of prey individuals, and may affect offspring performance through maternal effects. We investigated how timing of exposure to predation-related cues during early development affects offspring behavior after weaning. Females in the laboratory were exposed during pregnancy or lactation to one of three odor treatments: 1) predator odor (PO) originating from their most common predator, the least weasel, 2) odor produced by predator-exposed conspecifics, which we call conspecific alarm cue (CAC), or 3) control odor (C). We monitored postnatal pup growth, and we quantified foraging and exploratory behaviors upon exposure to each of the three odor treatments in 4-week-old pups. Exposure to odors associated with predation risk during development affected the offspring behavior, but the timing of exposure, i.e., pre- vs. postnatally, had only a weak effect. The two non-control odors led to different behavioral changes: an attraction to CAC and an avoidance of PO. Additionally, pup growth was affected by an interaction between litter size and maternal treatment, again regardless of timing. Pups from the CAC maternal treatment grew faster in larger litters; pups from the PO maternal treatment tended to grow faster in smaller litters. Thus, in rodents, offspring growth and behavior are seemingly influenced differently by the type of predation risk perceived by their mothers.